Pulmonary Aspergillosis Silently Presenting as Pneumothorax in Children with Leukemia: A Report of Three Cases. - Shah, Krunal; Kumar, Abhishek; Kumar, Arun; Kumar, Nuthan; Kaushik, Prakruthi; Thumallapalli, Avinash; Kumari, Bandagadde Srinivas Aruna; Appaji, Lingegowda (Indian Journal of Medical and Paediatric Oncology, 2022)
Aspergillosis causes invasive pulmonary disease in patients with hematological malignancies. Children with invasive pulmonary aspergillosis (IPA) usually have nonspecific radiographic findings unlike cavitary lesions commonly seen in adults. Pneumothorax due to rupture of peripheral fungal lesion may be a severe complication in patients with neutropenia. Here, we describe three children during induction chemotherapy for B-lymphoblastic leukemia with pneumothorax as a presenting feature of pulmonary aspergillosis.
Keywords: leukemia; pediatric oncology; pneumothorax; pulmonary aspergillosis